Unpacking Genetic Risk Pathways for College Student Alcohol Consumption: The Mediating Role of Impulsivity. (26th August 2019) - Ksinan, Albert J.; Su, Jinni; Aliev, Fazil; ,; Dick, Danielle M.
Abstract : Background: The period of college represents a particularly risky developmental stage with regard to alcohol use, as college students engage in more risky drinking behaviors than their noncollege peers, and such problematic alcohol use is associated with far‐reaching negative consequences. Existing findings from genome‐wide association studies (GWAS) indicate that alcohol consumption has a complex polygenic etiology. Currently, there is a lack of studies examining genetic risk for alcohol consumption using polygenic risk scores (PRS) in college samples. In this study, we examined whether alcohol‐specific and risky behavior–related PRS were longitudinally associated with alcohol consumption among college students and whether this effect might be partially mediated by impulsivity domains. Methods: The sample included n  =   2, 385 European ancestry (EA) and n  =   1, 153 African ancestry (AA) college students assessed over the course of 4 years. To indicate genetic risk, 2 PRS were created based on recent large‐scale GWAS: alcohol consumption (Liu et al., 2019) —drinks per week (DPW)‐PRS and risky behaviors (Linnér et al., 2019) —RISK‐PRS. The main outcome was alcohol consumption, measured across 4 waves of follow‐up data. The UPPS‐P impulsivity subscales were examined as mediators of the genetic effect on alcohol consumption. Results: The results from structural equation modeling showed that among EA students, both DPW‐PRS and RISK‐PRS had significant positive effects on alcohol consumption above and beyond UPPS dimensions and control variables. RISK‐PRS explained larger portion of variance in alcohol consumption than DPW‐PRS. RISK‐PRS showed a significant indirect effect on alcohol consumption through sensation seeking and lack of perseverance; no significant indirect effect of DPW‐PRS was found. No significant association of either PRS or alcohol consumption was found for AA participants. Conclusions: The current results found that PRS related to more broadly defined risky behaviors predicted alcohol consumption across college years and that this association was partially mediated via dimensions of impulsivity. Abstract : This study examined the longitudinal effect of genetic risk on alcohol consumption in a college sample followed across 4 years, and tested whether dimensions of impulsivity would mediate this association. The results showed that genotypic risk score based on broader risk‐taking behaviors predicted later alcohol consumption and its effect was partially mediated by several impulsivity dimensions. This information might inform alcohol prevention efforts by identifying at‐risk individuals early on in their lifespan, preferably before the onset of alcohol use.